Clinicopathological profile and yield of fibreoptic bronchoscopy in 30 cases of lung carcinoma - Chauhan, Jayant B.; Faruqui, Tehzeeb; Panchal, Pankaj (International Journal of Research in Medical Sciences, 2017)
Background: The study aims to identify the diagnostic yield of bronchoscopy along with clinico-pathological profile of 30 confirmed cases of lung cancer during a 6-months period. Methods: A retrospective analysis was conducted on the diagnostic yield bronchial brushing (BB), bronchoalveolar lavage (BAL) and brush biopsy specimens obtained at fibre-optic bronchoscopy for patients with lung cancer and their clinico-pathological characteristics studied. Results: Of 30 patients who underwent fibre-optic bronchoscopy examination brush cytology was diagnostic in 17 patients (68%) brush biopsy in 5 patients (20%) and BAL cytology in 4 patients (16%) with adenocarcinoma in 13 patients (43%), non-small cell carcinoma in 1 (3%), large cell carcinoma in 1 (3%), squamous cell carcinoma in 5 (16%), small cell carcinoma in 5 (16%). The most common Symptom was cough in 25 (83%) followed by chest pain in 22 (73.3%), breathlessness in 14 (46.6%), fever in 13 (43.3%), anorexia in 11 (36.6%), weight loss in 10 (33.3%), hoarseness of voice and haemoptysis in 5 (16.6%) and dysphagia in 1 (3.3%). Conclusions: In bronchoscopic procedure the highest yield is of brush cytology with adenocarcinoma being the most common type with presenting complaint of cough and chest pain. The prevalence of lung cancer is more common among males and commonly being located in right upper lobe.